The role of mindfulness in treating gaming addiction in high school students: A case study in Vietnam - Ha, Duong Thi Thu (Edelweiss Applied Science and Technology, 2024)
The objective of this study is to understand how mindfulness heals gaming addiction among high schoolers in Vietnam by sampling 200 individuals. The analyses thus performed are robust enough to reveal that multiples of psychological constructs related to mindfulness can influence the reduction of self-control, alleviation, related stress, and further emotional control, social and emotional skills, enhancement of focus and attention, motivation for a healthier diet, and reduction of dopamine dependence. The present results also show that this holds the functioning of mindfulness as a significant mediator in healing from gaming addiction, with additional correlations found among constructs. In this study, the increased break was found to contribute more to self-control, emotional regulation, and attention enhancement. This analysis shows that the model is valid and reliable, such that mindfulness interventions tend to mainstreamably nudge adolescents toward engaging in better behaviors. This study points out the necessity of incorporating mindfulness training in the treatment of gaming addiction and promises insights relevant to educators, policymakers, and mental health professionals that will be beneficial in aiding youth in their digital-age challenges with gaming.